2010
DOI: 10.1515/znc-2010-5-601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Novel Substituted and Unsubstituted N-(Benzoylphenyl)-1H-indole-2-carboxamides as Potent Antihypertriglyceridemic Agents

Abstract: The N-(benzoylphenyl)-1H-indole-2-carboxamide derivatives 1 -6 were synthesized, and the lipid-lowering effects of two of these novel compounds were studied using hyperlipidemic rats as an experimental model. Treatment of ethyl-1H-indole-2-carboxylate with aminobenzophenones in the presence of sodium ethoxide and DMF, followed by purifi cation using column chromatography, gave the target compounds in good yields. The tested animals were divided into control, hyperlipidemic, compounds 2-, 3-and bezafi brate-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(15 reference statements)
2
11
0
Order By: Relevance
“…These findings are in accordance with formerly published data. 11) In addition, the replacement of the heterocyclic aromatic rings with imidazole nucleus has led to compounds with improved water solubility in comparison with those already reported in the literature [7][8][9][10][12][13][14][15] as shown in the water solubility study test. The enhanced water solubility possibly contributes to the pharmacological activity improvement.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…These findings are in accordance with formerly published data. 11) In addition, the replacement of the heterocyclic aromatic rings with imidazole nucleus has led to compounds with improved water solubility in comparison with those already reported in the literature [7][8][9][10][12][13][14][15] as shown in the water solubility study test. The enhanced water solubility possibly contributes to the pharmacological activity improvement.…”
Section: Discussionmentioning
confidence: 86%
“…Synthesis Activation of both 1H-imidazole-5-carboxylic acid (1) and 4-methyl-1H-imidazole-5-carboxylic acid (8) in to the acyl chloride was obtained by using oxalyl chloride in excess in the presence of few drops of DMF. The mixture was refluxed under stirring for 90 min to give the corresponding imidazole carbonyl chloride (Charts 1, 2) according to a procedure reported by Berger.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study is to identify a new class of nicotinic acid carboxamide derivatives acting as a potential lipid lowering agents starting from nicotinic acid (niacin). The choice of carboxamide derivatives was based on results obtained by the same research group on indol carboxamide derivatives, where they found also that these compounds possessed lipid-lowering effects 11,12,23,24 . So in this study we decided to prepare a hybrid chemical scaffold of two effective hypolipidemic agents using a well-established nucleus (nicotinic acid nucleus) as our starting point to synthesize a novel nicotinic carboxamide derivative bearing the benzophenone unit of fenofibrate drug ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%